Definition of "Peasant Product" Category Based Preferences of Consumers in Santiago [Definición de la Categoría "Producto Campesino" en Base a Preferencias de Consumidores del Gran Santiago] - Saez-Tonacca, L; Ganga-Munoz, M (Universidad de Tarapaca, 2013)
Part of Development strategy aimed to support small farmers of in Chile and different Latin American countries, have proposed elaboration and selling of traditional food products, whose target are those consumers willing to pay a higher price compared to industrial food due to its particular quality attributes, nevertheless, lack of knowledge about which information consumers have about such attributes nor consumers judgment on traditional food quality, makes necessary to propose a category definition grouping food products made by peasants, and particularly processed food products. Information used in this study was reviewed secondary sources and primary data, through six focus groups and surveys, in this case, we defined a sample size of 660 people of socioeconomic ABC1 and C2, which use or have used products from the countryside. Attributes were identified related to the raw material, finished product, the process of development and producer. Results suggest that consumers purchase decision making is mainly defined by label information, specifically origin of the product and raw materials used for its elaboration. From results of this study, it is possible to define category of peasants processed food products, as those that are made directly by the producer, with intensive use of labor, based on a traditional homemade recipe-using raw materials of the season and from the processing site, with a color, aroma and taste of the product as close to raw materials and nutritionally beneficial to health, all accompanied by safety and quality in their processes.